RESTORATIVE MATERIAL PREFERENCE FOR POSTERIOR TEETH AMONG FINAL YEAR UNDERGRADUATE DENTAL STUDENTS IN MALAYSIAN PUBLIC UNIVERSITIES - Norazlina Mohammad; Noor Nabilah Mohamed; Nor Shazleen Mohd Ruzmi (Jurnal Penyelidikan Sains Sosial, 2020)
The trends of material selection for posterior restoration have changed and shifted from silver amalgam to composite restoration due to various reasons. It maybe expected that the dental curriculum in Malaysia would be following the same pattern. Thus, the aim of this study was to identify the types of posterior restorative material selection and factors that contribute to its selection. A total of 177 final year dental students from six Malaysian public dental schools responded to the questionnaire distributed online. Majority of the respondent acquired an equal knowledge and training on amalgam and composite restoration. However, they preferred composite to amalgam for posterior restoration (49.27% vs 35% respectively; p value<0.05). The major factor influencing choices of material are moisture control (92.1%). 77.4% agree that composite is a good substitutes for amalgam restoration but amalgam is still relevant and should not be totally replaced.